(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2025)
This research aims to determine the influential relationship between health information systems in its dimensions (independent variable) and the quality of health service in its dimensions, a dependent variable, as it was tested using the results of a field survey of a sample (226) of employees of the Nineveh Health Department. The Planning Department included (the Policy Division, the Statistics Division, and the Public Health, the Technical Matters Department, the Administrative, Financial and Legal Department, and the Inspection Department) and for the purpose of analyzing the responses of the members of the researched sample, they were tested with ready-made standards and various statistical tools to suit the requirements of the research, relying on the statistical program (SPSS, V26) to infer percentages, arithmetic means, standard deviations, and coefficients. Variation, response intensity, measurement reliability, common method bias, and internal consistency. The statistical program (Amosv26) was also used to analyze the influence relationship, and the descriptive and analytical approach was used as a scientific method in the research. In order to excel in the quality of health service, the health organization must develop the level of quality of health service provided by adopting information systems as an important input in enhancing quality in a way that achieves the expectations of beneficiaries for the level of quality of health service or exceeds those expectations. The study found that there is a significant direct impact relationship at the macro and micro levels of health information systems on the quality of health services. The research recommended the need to pay attention to health information systems as they are the basic building block for making the appropriate decision and to take advantage of the available resources available in our health organizations to improve the level of quality of health service provided to beneficiaries.